Enhancing Learning for Medical Students in Psychiatry—Ethnographic Explorations - Fog-Petersen, Cecilie; Borgnakke, Karen; Arnfred, Sidse (Acta Paedagogica Vilnensia, 2017)
We describe an ongoing study investigating the main learning conditions for medical students during clinical attachment in psychiatry. The focus is on how a new video library is used in practice as a supplementary learning tool. The study is based on ethnographic methods and draws on Lave and Wenger, Dreyfus and Dreyfus, and Dewey. The article provides examples of empirical studies and briefly elaborates on the challenges of the chosen methods.